A fundamental comprehension and recent progress in advanced Pt‐based ORR nanocatalysts. (3rd March 2021) - Wang, Yao; Wang, Dingsheng; Li, Yadong
Abstract: Today, Pt/C catalysts are widely used in proton exchange membrane fuel cells (PEMFCs). The practical applications of PEMFCs still face many limitations in the preparation of advanced Pt‐based catalysts, including high cost, limited life‐time, and insufficient power density. A kinetically sluggish oxygen reduction reaction (ORR) is primarily responsible for these issues. The development of advanced Pt‐based catalysts is crucial for solving these problems when the large‐scale application of PEMFCs is to be realized. Herein, we demonstrate the design principle of advanced Pt‐based catalysts with an emphasis on theoretical understandings to practical applications. Generally, three main strategies (including strain effect, electronic effect, and ensemble effect) that governing the initial activity of Pt‐based electrocatalysts are elaborated in detail in this review. Recent advanced Pt‐based ORR catalysts are summarized and we present representative achievements to further reveal the relationship of excellent ORR performance based on theoretical mechanisms. Then we focus on the preparation standards of membrane electrode assembles and testing protocols in practice. Finally, we predict the remaining challenges and present our perspectives with regards to design strategies for improving ORR performance of Pt‐based catalysts in the future. Abstract : The development of advanced Pt‐based catalysts is crucial for solving these problems if the large‐scale application of proton exchange membrane fuel cells (PEMFCs) is to be realized. Thus, a comprehensive understanding of the fundamental principle and design strategy is of great importance for advancing new generation Pt‐based nanocatalysts.